FOURIER-TRANSFORM INFRARED SPECTROSCOPY ANALYSIS OF MAULI BANANA (MUSA ACUMINATA) EXTRACT AS A POTENTIAL PULP WOUND HEALING - Dewi Puspitasari; Muhammad Yanuar Ichrom Nahzi; Yosi Kusuma Eriwati; Erni Marlina; Maharani Laillyza Apriasari; Maria Tanumihardja; Juliyatin Putri Utami; Amy Nindia Carabelly (FKG Unlam, 2023)
Background: Pulp wound healing is a critical aspect of endodontics, aiming to preserve the vitality and function of dental pulp tissues. Natural compounds have gained attention for their potential therapeutic applications in dentistry. Mauli banana (Musa acuminata) is a tropical fruit in South Kalimantan as one of the natural plants that have the ability as antibacterial, antifungal, anti-inflammatory, antioxidant, and immunomodulatory effects contains various bioactive molecules with potential pulp wound healing properties. Purpose: to identify and evaluate the functional groups present in mauli banana stem extracts. Methods: This study is true experimental research, the samples were mauli banana stem that were extracted with maceration technique and were subjected to Fourier-Transform Infrared Spectroscopy test. Results: Identification of functional groups of organic compounds from mauli banana are as follows: a) Peak 3638.95 cm-1 show O-H (nonbonded hydroxy group, OH stretch primary) component alcohol, b) Peak 3265.82 cm-1is C-H (alkane), c) Peak 2928.09 cm-1 refer to OH (carboxylic acid hydrogen bonds) and aldehydes groups, d) peak 1571.35 cm-1 refers to amide, C=O - asymetric stretching, e) peak 1400.82 cm-1, refers to CO2- symetric stretching and carboxylate (carboxylic acid salt) CH2 scissoring, f) peak 1030.17 cm-1 refers to C=C (alkanes), aliphatic phosphate, g) Peak 520.53 cm-1 refers to inorganic phosphates. Conclusion: FTIR spectra analysis of mauli banana stem extract show the presence of O-H hydroxy groups, aldehydes groups, carbonyl groups, aliphatic groups, carbonyl groups, amides groups and C-O stretching vibrations suggests that the extract contains various bioactive molecules with potential pulp wound healing properties.